If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8p + -3(6 + -6p) = 6(p + -4) + -18 -8p + (6 * -3 + -6p * -3) = 6(p + -4) + -18 -8p + (-18 + 18p) = 6(p + -4) + -18 Reorder the terms: -18 + -8p + 18p = 6(p + -4) + -18 Combine like terms: -8p + 18p = 10p -18 + 10p = 6(p + -4) + -18 Reorder the terms: -18 + 10p = 6(-4 + p) + -18 -18 + 10p = (-4 * 6 + p * 6) + -18 -18 + 10p = (-24 + 6p) + -18 Reorder the terms: -18 + 10p = -24 + -18 + 6p Combine like terms: -24 + -18 = -42 -18 + 10p = -42 + 6p Solving -18 + 10p = -42 + 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. -18 + 10p + -6p = -42 + 6p + -6p Combine like terms: 10p + -6p = 4p -18 + 4p = -42 + 6p + -6p Combine like terms: 6p + -6p = 0 -18 + 4p = -42 + 0 -18 + 4p = -42 Add '18' to each side of the equation. -18 + 18 + 4p = -42 + 18 Combine like terms: -18 + 18 = 0 0 + 4p = -42 + 18 4p = -42 + 18 Combine like terms: -42 + 18 = -24 4p = -24 Divide each side by '4'. p = -6 Simplifying p = -6
| n+14=8 | | 5x-11y=13 | | 12/n^2-16 | | 3k^2-16k=4 | | 45+x=73 | | .8x=.7x+4 | | 18x^4-39x^2+20=0 | | 12y^3-2y^2= | | X^4+16X+16=0 | | 10x^3+8x^2+14x= | | F(x)=16x^4-8x^3+90x^2-32x+104 | | 2(2+x)=4-(x-2) | | r-2s=15fors | | 4.5+x=9 | | 9^2n=1/27^n--5 | | -55=5(v-9) | | 6w-2=40 | | 5(v-9)=-55 | | 30+19b=24b | | 6.3+(-.4)y+y=9 | | 96=2x^2 | | 35/16=x | | tan(x)=-8.4 | | 2z^4-2=0 | | -1/4x-12=x+3 | | 0.15y+0.05(y+6000)=1900 | | 4y+4x=28 | | 2.5=x^3+x^4 | | -6.93-14.6k=15.27-12.6k | | x^3+2x^2-36x-73=0 | | 18x^3-90x^2-432x=0 | | F(x)=5x^2+20x+33 |